Mechanisms of Substance Transport Across the Cell Membrane: Diffusion, Osmosis, and Active Transport - Azizah Amalia Abbas; Lutfitri Rahmadani; Fransiska Petronela Sepe; Yohanes Mari Ba'i Leta; Veronika P. Sinta Mbia Wae (Jurnal Biologi Tropis, 2026)
The cell membrane is a semipermeable structure that regulates substance exchange between intracellular and extracellular environments, maintains cellular homeostasis, and supports metabolic processes, yet the fundamental mechanisms of diffusion, osmosis, and active transport are still frequently misunderstood in both theoretical and educational contexts. This study aims to comprehensively review substance transport mechanisms across the cell membrane and their relevance to biology education and contemporary cellular research. This research employed a narrative literature review, analyzing scientific books and peer-reviewed journal articles published within the last five to ten years, selected from databases such as Google Scholar, PubMed, and MDPI based on topic relevance. The results indicate that diffusion facilitates molecular movement along concentration gradients either directly or through transport proteins; osmosis regulates water balance through semipermeable membranes mediated by aquaporins; and active transport enables the movement of ions and molecules against concentration gradients through ATP-dependent pumps, secondary transporters, ABC transporters, and V-ATPase. These mechanisms are interconnected and influenced by membrane composition, molecular characteristics, and transporter–substrate interactions. This review highlights the importance of an integrative understanding of membrane transport processes to strengthen conceptual learning in biology education and to support advancements in cellular and biomedical research.